(untitled) - Coble, Colleen (Nashville, Tennessee, 2020)
"Police Chief Jane Hardy is still reeling from the scandal that rocked her small-town department just as she took over for her retired father - the man who wrecked her life with one little lie. Now shes finally been reunited with her presumed-dead fifteen-year-old son, Will, and his father, documentarian Reid Bechtol. When a murder aboard the oil platform Zeus exposes an environmental terrorists plot to flood Mobile Bay with crude oil, Jane and Reid must put their feelings for each other behind them and work together to prevent the rig from being sabotaged"-- Provided by publisher.
Keywords: Hardy, Jane; (Fictitious character); Fiction; Man-woman relationships; Murder; Fiction; Fiction; Women police chiefs; Fiction; Fiction; Terrorists; Alabama; Fiction; Thrillers (Fiction); Romantic suspense fiction; Religious fiction